2023
DOI: 10.3389/fnimg.2023.1129587
|View full text |Cite
|
Sign up to set email alerts
|

Measuring white matter microstructure in 1,457 cannabis users and 1,441 controls: A systematic review of diffusion-weighted MRI studies

Abstract: IntroductionCannabis is the most widely used regulated substance by youth and adults. Cannabis use has been associated with psychosocial problems, which have been partly ascribed to neurobiological changes. Emerging evidence to date from diffusion-MRI studies shows that cannabis users compared to controls show poorer integrity of white matter fibre tracts, which structurally connect distinct brain regions to facilitate neural communication. However, the most recent evidence from diffusion-MRI studies thus far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 162 publications
1
5
0
Order By: Relevance
“…This is a vital neural junction that supports both fundamental and complex mental processes from attention to memory and social cognition (52), highlighting the signi cance of related WM pathways for neural communication to this region. We did not observe evidence of associations between WM metrics and any cognitive or mental health outcomes, which is in line with the recent systemic review by Robinson et al (53). However, we observed a signi cant association between total cannabis consumption (the last month prior to study) and the strength of connectivity between left lateral orbitofrontal cortex and right inferior parietal lobe.…”
Section: Discussionsupporting
confidence: 91%
“…This is a vital neural junction that supports both fundamental and complex mental processes from attention to memory and social cognition (52), highlighting the signi cance of related WM pathways for neural communication to this region. We did not observe evidence of associations between WM metrics and any cognitive or mental health outcomes, which is in line with the recent systemic review by Robinson et al (53). However, we observed a signi cant association between total cannabis consumption (the last month prior to study) and the strength of connectivity between left lateral orbitofrontal cortex and right inferior parietal lobe.…”
Section: Discussionsupporting
confidence: 91%
“…Our study is the first to integrate white matter microstructural integrity into the multiple levels of impairment that SUD patients exhibit in Low FA values typically reflect low coherence of the linear microstructure of white matter tracts. 42 As presumed outcomes of the toxic effect of substance use, studies demonstrated that FA values decrease with heavy 43 or long-term drinking, 44 continued smoking 45 and cannabis use 46 generally with lower scores being linked to poorer clinical outcomes. In our study, lower FA values in clusters encompassing the callosal genu and body and the bilateral anterior corona radiata were linked to poorer mean inhibition performance assessed via mobile Stroop testing in the SUD sample.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic use, for example, has been reported to increase tract FA ( 81 , 82 ), while others have reported a subtle loss of white matter integrity ( 83 ). Diffusion studies have also found poorer integrity of white matter in cannabis users compared to non-users ( 84 , 85 ). In addition, potential protective factors for white matter abnormalities including psychotherapy ( 86 , 87 ) or cognitive training ( 88 ) may have been a confounder in our study, and such data were unavailable from our participants for analyses.…”
Section: Discussionmentioning
confidence: 99%